Factors influencing the integration of planetary health topics into undergraduate medical education in Ireland: a qualitative study of medical educator perspectives - Aisling Walsh; Oisin Brady Bates; Debbi Stanistreet (BMJ Open)
Aims Planetary health is a transdisciplinary field that explores the relationship between the escalating climate and environmental crises and human health. In light of the human health cost arising from planetary health issues, there is a need to educate future medical practitioners accordingly. This study investigates the factors influencing the integration of planetary health into undergraduate medical education at an Irish university and makes recommendations for future practice.Methods A qualitative descriptive study design was employed. Twelve semi-structured interviews were conducted with academic staff actively involved in teaching on the undergraduate medical curriculum at Royal College of Surgeons in Ireland University of Medicine and Health Sciences. Both barriers and facilitators to integrating planetary heath into the curriculum were explored. Braun and Clarke’s thematic analysis was used to analyse the findings.Results Barriers to integration include: a lack of curricular space, a perceived lack of awareness among students and educators and a potential lack of knowledge among educators and senior management in relation to these issues. These barriers were tempered by significant facilitators suggesting a shifting paradigm within institutions, innovative approaches to content delivery and an increasing demand from undergraduate medical students.Conclusion This study found a demand from medical educators for the integration of planetary health topics into the medical curriculum. It is suggested that significant adaptation of existing medical curricula is required both in Ireland and further afield, to meet this need. Recommendations based on the barriers and facilitators that emerged during the analysis include: emphasising the clinical relevance of these topics, as suggested by the current evidence base; promoting senior and departmental leadership; and emphasising the potential for improvements in institutional prestige.